Critical Evaluation of Mouse Models Used to Study Pain and Loss of Pain Perception in Diabetic Neuropathy - Bierhaus, A.; Nawroth, P. P. (Experimental and Clinical Endocrinology & Diabetes, 2012)
A number of studies have addressed diabetic neuropathy (DN) in transgenic and knock out mouse models to unravel the molecular mechanisms underlying metabolic pain and loss of pain perception. However, it is difficult to compare these studies with each other or even with human DN due to experimental differences including the type of diabetes, the background strain of the respective mouse model, the methods of diabetes induction and the duration of diabetes, animal age and gender. To receive useful information for DN from genetically modified mice, it is therefore mandatory to first define the appropriate model and – if necessary – to backcross transgenic strains into the respective background to allow a reliable (and at least in part translatable to human DN) interpretation of the results.
Keywords: diabetes; neuropathy; animal models